Planktonic foraminifera biozones and isotope stratigraphy of the Cenomanian-Turonian boundary in the western part of the Kopet-Dagh Basin, NE Iran. (November 2018) - Ezampanah, Yadolah; Sadeghi, Abbas; Scopelliti, Giovanna; Adabi, Mohammad Hossein; Jamali, Amir Mohammad
Abstract: A biostratigraphic study based on the planktonic foraminifera and isotope stratigraphy of the Cenomanian-Turonian interval has been undertaken in the western part of the Kopet-Dagh Basin (NE Iran). In this research, two stratigraphic sections including: Maraveh Tappeh and Qareh Galdy have been sampled and studied. Based on planktonic foraminifera, three biozones were assigned to this interval. These are the Rotalipora cushmani Zone, Whiteinella archaeocretacea Zone and Helvetoglobotruncana helvetica Zone, These biostratigraphic data confirm a gradual faunal turnover of planktonic foraminifera, at the Cenomanian-Turonian boundary in Whiteinella archaeocretacea Zone characterized by: absences, low abundance and disappearances of complex morphotypes. After this event, in Helvetoglobotruncana helvetica Zone, along with simple globular chamber morphotypes, single keeled and double-keeled morphotypes appeared and flourished. The carbon-isotope curves in both sections, record a negative shift values below the Aitamir-Abderaz formations boundary in Whiteinella archaeocretacea Zone, and then, a positive excursion of about 5.50‰, along with several fluctuations are well evident in both sections. The δ 18 O values show, from the bottom to the top, a gradual increase of averagely 2‰. Based on these results, the Cenomanian-Turonian succession in this part of the Kopet-Dagh Basin is continuous and corresponds to the siltstone and chalky limestone layers of the upper part of the Aitamir Formation and the lower part of the Abderaz Formation. Highlights: The Cenomanian-Turonian boundary is defined based on planktonic foraminifera. 29 species belonging to 9 genera and three biozones of Cretaceous of planktonic foraminifera were recognized. New middle Cretaceous (Cenomanian-Turonian boundary) paleoenvironmental conditions were reconstructed in this part of Tethys ocean based on the O, C stable isotopes. A positive excursion of about 5.50‰, along with several fluctuations, are well evident in both sections.